Students perception and interest on chemistry: Learning evaluation integrated quizziz media - Nelius Harefa; Marudut Sinaga; Saronom Silaban (Pascasarjana Universitas Negeri Medan, 2020)
Interest in learning is a passion or a great desire for something that is closely related to personality, motivation, expression and self-concept, identification, heredity, and external factors. Interest in learning affects the cognitive, affective, and psychomotor aspects of students. In this study, analyzed and interpreted student interest in learning through media-based learning Quizizz and students' perceptions of the media. Based on the analysis and interpretation of the data, indicators of student interest in the media Quizizz increased by 0.818 in the high category, indicators of student attention increased by 0.555 in the medium category, indicators of feelings of pleasure increased by 0.684 in the medium category, and indicators of student involvement increased by 0.599 in the medium category. Also, 76.32% of students thought that Quizizz media were very interesting, 50% thought that Quizizz media were easily applied, 86.84% thought that Quizizz media accommodate students to compete fairly, and 44.74% thought that Quizizz media were practically applied. Thus, students have a good perception of the Quizziz media accompanied by increased interest in learning.Keywords: Learning evaluation, Students’ perceptions, Students’ interest, Quizziz media